The Relationship between Diabetes Mellitus and Hypertension with Pemphigus Vulgaris in Pemphigus Vulgaris Patients - Muhamad Firdaus; Gardenia Akhyar; Amel Yanis (Indonesian Journal of Global Health Research, 2025)
Pemphigus vulgaris (PV) is a chronic autoimmune skin disease that manifests as loose vesicles and bullae that affect the mucosa and skin. The first-line therapy for PV is systemic corticosteroids. Although corticosteroid therapy is effective as treatment for pemphigus vulgaris, long-term use of corticosteroids causes various complications such as diabetes mellitus and hypertension. Objectives to examine the relationship of pemphigus vulgaris with diabetes mellitus and hypertension. This study is a retrospective analytic study with a cross sectional approach with a sample size of sixteen people with pemphigus vulgaris. This research was conducted in March – August 2022 at Dr. M. Djamil Hospital in Padang. Relationship analysis is performed using Fisher's exact test by comparing the incidence of diabetes mellitus and hypertension in patients with pemphigus vulgaris with patients with other autoimmune bullous diseases. There is no significant relationship between pemphigus vulgaris and diabetes mellitus (p = 0.133) and hypertension (p = 0.253). The profile of patients with pemphigus vulgaris is also obtained: the annual incidence of PV is 3.2 cases/year; the majority of PV patients are women, with a female to male ratio of 1:0,78; the majority of PV patients are in the 40-60 year age group; the occupation of the most PV patients is housewives; and the majority of clinical manifestations of patients with PV are found on the skin and mucous membranes. There is no significant relationship between pemphigus vulgaris with diabetes mellitus and hypertension.